Measuring Arterial Stiffness in Animal Experimental Studies. Issue 5 (May 2020) - Butlin, Mark; Tan, Isabella; Spronck, Bart; Avolio, Alberto P.
Abstract : The arterial wall is a composite material of elastin, collagen, and extracellular matrix with acutely modifiable material properties through the action of smooth muscle cells. Therefore, arterial stiffness is a complex parameter that changes not only with long-term remodeling of the wall constituents but also with acute contraction or relaxation of smooth muscle or with changes in the acute distending pressure to which the artery is exposed. It is not possible to test all these aspects using noninvasive or even invasive techniques in humans. Full characterization of the mechanical properties of the artery and the specific arterial factors causing changes to stiffness with disease or modified lifestyle currently require animal studies. This article summarizes the major in vivo and ex vivo techniques to measure the different aspects of arterial stiffness in animal studies.